1992
DOI: 10.1002/cber.19921250144
|View full text |Cite
|
Sign up to set email alerts
|

A Mass‐Spectrometric Investigation of CxNO2 (x=1, 2) Ions and Neutrals

Abstract: 4 LThe isomeric [C2,N,02]+ ions OCNCO+, OCCNO+, and NCCO, have been generated and structurally characterized on the basis of their collisional activation, charge reversal, and neutralization-reionization mass spectra. The open-shell neutrals formed in the neutralization step undergo facile unimolecular decomposition. A recovery signal is obtained only for OCCNO.1. --In recent years, we have used the technique of neutralization-reionization mass spectrometry ['] to characterize cumulenes of theoretical and cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
3
16
0
2
Order By: Relevance
“…Detection of a fragment ion [OCNCO] + ( m/z 70) that failed to retain a single hydrogen atom, was surprising (Scheme 2). Structure and reactivity of this ion have been repeatedly investigated in the past [4552]. Our CID MS/MS experiments of the mass-selected ion with m/z 70 produced following the fragmentation of protonated triuret revealed that its structure is "linear" as shown on Scheme 2 and its MS/MS spectrum is consistent with that reported earlier for a similar structure [47, 48].…”
Section: Resultssupporting
confidence: 83%
“…Detection of a fragment ion [OCNCO] + ( m/z 70) that failed to retain a single hydrogen atom, was surprising (Scheme 2). Structure and reactivity of this ion have been repeatedly investigated in the past [4552]. Our CID MS/MS experiments of the mass-selected ion with m/z 70 produced following the fragmentation of protonated triuret revealed that its structure is "linear" as shown on Scheme 2 and its MS/MS spectrum is consistent with that reported earlier for a similar structure [47, 48].…”
Section: Resultssupporting
confidence: 83%
“…[1] OCNCO has so far only been observed in the mass spectrometer as a decomposition product of various molecules generated by electron impact ionization. [2] An ion generated as such, which was initally assumed to be linear, reacts in the mass spectrometer with pyridine forming 1:1 and 1:2 adducts, in which the OCNCO moiety is now assumed to be bent. [3] The starting point for our synthesis was the idea to generate the OCNCO ion in the form of a salt by Cl À or F À abstraction from ClÀCOÀNCO and FÀCOÀNCO with strong Lewis acids.…”
mentioning
confidence: 99%
“…[7] Experimental Section FÀCOÀNCO was prepared in 70 % yield from ClÀCOÀNCO by halogen exchange with an excess of SF 3 /SbCl 5 at 75 8C. The product must be removed immediately from the reaction vessel in order to avoid decomposition into COF 2 and OC(NCO) 2 . The latter polymerizes under these conditions.…”
mentioning
confidence: 99%
“…[1] OCNCO ist bisher nur im Massenspektrum als durch Elektronenstoûionisation erzeugtes Zerfallsprodukt verschiedener Moleküle nachgewiesen worden. [2] Ein so erzeugtes Ion, dem zunächst eine lineare Geometrie zugeschrieben wurde, reagiert im Massenspektrometer mit Pyridin zu 1:1-und 1:2-Adukten, für die nunmehr nichtlineare OCNCO-Geometrien angenommen werden. [3] Ausgangspunkt unserer Synthese war die Idee, durch Cl Àoder F À -Abstraktion von ClÀCOÀNCO und FÀCOÀNCO mit starken Lewis-Säuren Salze des OCNCO -Ions zu erhalten.…”
Section: Isolierung Und Struktur Des Ocnco -Ions**unclassified
“…[1] Trotz der Bedeutung solcher Verbindungen für viele Katalyseprozesse, bei denen sie häufig viel höhere Aktivitäten als Übergangsmetallhydride aufweisen, sind die meisten dieser Verbindungen Ln III -Komplexe, die den Cyclopentadienylliganden oder dessen substituierte Analoga enthalten. Folgende Lanthanoidhydride mit zweiwertigen Metallzentren sind bekannt: Borhydridkomplexe des Typs [Ln{(m-H) 3 BH} 2 (CH 3 CN) n ] (Ln Yb, n 4; Ln Eu, n 2), [2] Trialkylboran-stabilisierte Hydride des Typs [Ln(Tp tBu,Me )-(HBEt 3 )(thf) n ] (Ln Sm, n 0; Ln Yb, n 1), [3] die Hydrid- [5].…”
Section: Isolierung Und Struktur Des Ocnco -Ions**unclassified